PERANAN MEDIA PEMBELAJARAN TERHADAP MINAT SISWA DALAM PEMBELAJARAN PPKN - Hanif, Muhamad Hanif Ramadhan; Suci, Astutti Suci Arti Aisyah (SEHRAN (Jurnal Pendidikan Sejarah dan Kewarganegaraan), 2024)
In learning Pancasila and Citizenship Education, the function of learning media plays a crucial role. Several types of learning media that can be developed and applied in the Civic Education learning process are 1) Visual Media, 2) Audiovisual Media, and 3) Multimedia. Learning media is not only a complement to the learning process but also one of the determining factors for the success of the learning process in the classroom. Choosing the right type of learning media can facilitate the transfer of material from teacher to student, making the learning process more effective and efficient. Learning media not only impacts students' cognitive development but also helps develop their imagination and skills. These five functions illustrate the positive impact of learning media on the learning process. Learning media serves several functions, including communication, motivation, meaningfulness, equalizing perceptions, and addressing individuality. Each of these three types of media has its own advantages and disadvantages.